KONSEP ADVERSITY QUOTIENT (AQ) DALAM MENGHADAPI COBAAN (DITINJAU DARI PERSPEKTIF AL-QUR’AN DAN HADIS) - mahmudah mahmudah; Fatimah Zuhriah (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2021)
Islam makes the Al-Qur'an and Hadith as guidelines and instructions in living the life of every human being. Allah will always test His servants both in happiness and in difficulty. Lack of attention to psychological aspects makes many individuals wrong in taking action when faced with difficulties. Dr. Paul G. Stoltz initiated the adversity quotient, this field is a scientific tool for improving individual responses in the face of adversity. This concept is relevant and applicable today, because IQ, EQ and SQ alone are still not sufficient to achieve life success. Based on this, the purpose of this study is to determine the concept of adversity quotient in facing trials from the perspective of Al-Qur'an and Hadith. The method used is literature study. In this study, data sources were obtained from relevant literature such as books, journals, or scientific articles related to the selected topic. The results showed that the concept of adversity quotient in facing trials when viewed from the perspective of the Al-Qur'an Hadith has relevance to the elements contained in patient attitude. The conclusion of this research is that the concept of adversity quotient in the view of Islam is a person who is able to be patient and optimistic and never give up in facing every trial.